Distributed on-demand multi-optional routing protocol in multi-hop wireless networks - Chughtai, O. (Institute of Electrical and Electronics Engineers Inc., 2015)
In Wireless Sensor Networks (WSNs), fair utilisation of the network resources is a challenging task. In this regard, one of the determining factors is the routing protocol that plays an important role to route the data traffic from the source to the destination, under limited network resources. Most of the routing protocols and their variants in WSNs replace the routing metric of the prevalent routing protocol with their proposed routing metric and keep the route discovery mechanism intact. However, replacing only the routing metric is insufficient to improve the performance of the entire network as it can generate high End-to-End (ETE) delay in finding the destination as per the routing criteria. In this paper, a novel single path loop-free Distributed On-demand Multi-Optional routing (DOMO) protocol is presented. The DOMO selects the best sensor node based on the routing metric(s) amonst various alternatives at each stage during forward route formation. A simulation has been performed in ns-2.35 and it has been observed that, using the same routing metric(s), DOMO performs better for long-term communication in WSNs as compared to Ad hoc On Demand Distance Vector (AODV). The results have revealed that DOMO improves the average ETE delay by 17 and normalises the routing load by 47 as compared to AODV. Â© 2014 IEEE.